Highly efficient and sustainable removal of Cr (VI) in aqueous solutions by photosynthetic bacteria supplemented with phosphor salts. (November 2021) - Su, Yan-Qiu; Yuan, Shu; Guo, Yuan-Cheng; Tan, Yong-Yao; Mao, Hao-Tian; Cao, Yi; Chen, Yang-Er
Abstract: Photosynthetic bacteria have flexible metabolisms and strong environmental adaptability, and require cheap, but plentiful, energy supplements, which all enable their use in Cr(VI)-remediation. In this study, the effects of culture conditions on the total Cr removal rate were investigated for a newly identified strain of Rhodobacter sphaeroides SC01. The subcellular distribution and Cr(VI) reduction ability of four different cellular fractions were evaluated by scanning electron microscopy and transmission electron microscopy. Experiments indicated that the optimal culture conditions for total Cr removal included a culture temperature of 35 °C, pH of 7.20, an NaCl concentration of 5 g L −1, a light intensity of 4000 lx, and an initial cell concentration (OD680 ) of 0.15. In addition, most Cr was found in the cell membrane in the form of Cr (III) after reduction, while cell membranes had the highest Cr(VI) reduction rate (99%) compared to other cellular components. In addition, the physical and chemical properties of SC01 cells were characterized by FTIR, XPS, and XRD analyses, confirming that Cr was successfully absorbed on bacterial cell surfaces. CrPO4 ‧6H2 O and Cr5 (P3 O10 )3 precipitates were particularly identified by XRD analysis. After screening supplementation with five phosphor salts, Cr(VI) reduction due to bioprecipitation was improved by the addition of Na4 P2 O7 and (NaPO3 )6 salts, with the Cr(VI)-reduction rate combined with Na4 P2 O7 addition being 15% higher than that of the control. Thus, this study proposes a new Cr(VI)-removal strategy based on the combined use of photosynthetic bacteria and phosphor salts, which importantly increases its potential application in treating wastewater. Graphical abstract: Image 1 Highlights: Cell membrane accumulated most of Cr and presented the highest Cr(VI) reduction rate. Cr(III) existed as Chromium Phosphate Hydrate and Chromium Phosphate in SC01. Na4 P2 O7 and (NaPO3 )6 could promote the reduction of Cr(VI). Cr(VI) reduction rate adding Na4 P2 O7 was 15% higher than that of the control.